Pengaruh Pendekatan Contextual Teaching and Learning (Ctl) Terhadap Hasil Belajar PKn Siswa di Sekolah Dasar - Maifitri, Anisa; Reinita, Reinita; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims to determine the influence of Contextual Teaching and Learning (CTL) to result study of students in learning PKN in Class V SDN 04 Garegeh Bukittinggi City. This research is a type of experimental research in the form of Quasy Experimental Design. Sample of the research is class VA and VB. The coubting result of research of data that used is t test founded tcount > ttable, t test 2,342 > 1,671 at α level of 0,05. So that, it can be concluded that there is a significant influence in using of Contextual Teaching and Learning (CTL) to result study of students in learning PKN in Class V SDN 04 Garegeh Bukittinggi City. Key words: of Contextual Teaching and Learning, Result study, PKn